GOING BEYOND FIRST IMPRESSIONS*: JANE AUSTEN ON THE SPOTLIGHT - Ferreira, Carla Alexandra [UNESP] (Univ Federal Santa Catarina, Programa Pos-graduacao & Letras-ingles, 2017)
The last decades has seen a proliferation of Jane Austen's novels for television and cinema. Despite being an important movement for the popularity of her literary work that has also brought some problems for a serious understanding of Austen's literary project. The purpose of this essay is to point out the need of considering the changes, preferences and omissions, apparently not very important or carried out because of some demands of the translation from a novel to the cinema, that occur when her work is revisited. We will try to show some choices made in the transference from her novels to film may erase part of the writer's fictional project which is among other things to portray women's role in the nineteenth century patriarchal English society and try to change women's condition of invisibility that had been created and spread since Enlightenment. In order to illustrate our point the 2005 version of Pride and Prejudice for the cinema will be used.
Keywords: Jane Austen; adaptation; gender; periodization